Interactions between plant growth promoting microorganisms (PGPM) and biochar - ABDUL MUTALIB, ASILAH (2018)
Rhizobia are frequently used in the agriculture sector to enhance legume growth and improve soil fertility. There is growing interest in utilizing biological nitrogen fixation as a means of increasing the potential for sustainable intensification of food production whilst simultaneously reducing environmental damage caused by overuse of chemical fertilisers. Biochar, a recalcitrant carbon-rich product of pyrolysis which may be added to soil as a fertilizer or as a soil improver, alters soil physico-chemical properties usually by acting as a liming agent, by increasing water holding capacity or by modifying cation exchange capacity. The effects of biochar on the soil microbial community are not fully understood. Therefore, the main aim of this investigation was to evaluate the effects of biochar on the Rhizobium-legume relationship and determine whether biochar could increase legume growth. To achieve this aim, a series of growth experiments were carried out under controlled conditions in which broad bean (Vicia faba) was grown with Rhizobium leguminosarum and the symbiosis tested against three concentrations of biochar applied as a soil amendment and with two different char particle sizes. Beans responded well to Rhizobium under char-free conditions but the effects of biochar on the symbiosis were variable and depended on char particle size, concentration and Rhizobium strain (commercial or indigenous). Powdered char inhibited plant growth when in the presence of the commercial rhizobia, but not with indigenous strains. This is an important finding since commercial inocula are commonly used in agronomic situations. Plant available soil nutrients were modified by biochar and surprisingly by an interaction between char concentration and the two rhizobia strains. When beans were co-cropped with wheat, beans performed better when grown with powdered char than without. This is in contrast to the response of bean plants to powdered char in the absence of any competition. Since wheat was generally the superior competitor, powdered char amendment enabled the bean to take advantage of the N-limiting environment that powdered char created and perform better than in the soils that advantaged the wheat. The investigation highlighted the complexity of the system, but identified the importance of char particle size and Rhizobium strain selection.